Ambarzumyan Theorem for Conformable Type Sturm-Liouville Problem on Time Scales - Yar, Ayşe Çiğdem; Gulsen, Tuba; Yılmaz, Emrah (My University, 2024)
In this study, we give an Ambarzumyan type theorem for a Sturm-Liouville dynamic equation which includes conformable type derivative on time scales with conformable Robin boundary conditions. Under certain conditions, we prove that potential function can be determined by using only first eigenvalue.
Keywords: Conformable Derivative; Ambarzumyan Theorem; Sturm-Liouville Equation; Time Scale.